Detection of GBV-C/HGV RNA in cervico-vaginal smears from healthy individuals - Watanabe,Maria Angelica Ehara (2008)
The purpose of the present study was to evaluate the sexual transmission of GBV-C/HGV, through RNA detection in cervicovaginal smears. Therefore the GBV-C/HGV RNA in cervicovaginal smears from apparently healthy women was investigated using routine proceedings for prophylactic screening to cervical cancer. GBV-C/HGV RNA was detected by reverse transcriptase and polymerase chain reaction (RT-PCR). Only one woman presented co-infection with human papilloma virus (HPV). The GBV-C/HGV RNA was detected in 13/73 (17.57%) healthy women and it's prevalence in participating women between 28-43 years old was 53.85%. No association was found with GBV-C/HGV for the age of first sexual intercourse and number of pregnancies. In GBV-C/HGV RNA positive women, 69.23% were married. In conclusion, the present findings show that cervical and vaginal specimens could contain the GBV-C/HGV RNA.